KINERJA PEGAWAI TRANSPORTASI UDARA BADAN PENELITIAN DAN PENGEMBANGAN PERHUBUNGAN DIPENGARUHI OLEH KEPEMIMPINAN MELALUI DISIPLIN KERJA - Edy Sanusi Silitonga (Program Studi Magister Manajemen Fakultas Ekonomi Universitas Krisnadwipayana, 2022)
This study aims to determine the performance of employees in the air transportation of the Research and Development Agency for Transportation is influenced by leadership through work discipline. This study was conducted using the quantitative method by distributing questionnaires to air transportation employees Research and Development Agency. In this study the researcher used the saturated sample method where the sample used was all 46 employees of the population. For the analysis method the researcher uses a path analysis test (path analysis). The results showed that leadership had a positive and significant effect on employee performance. Work discipline has a positive and significant effect on employee performance. Leadership has a positive and significant effect on work discipline. And leadership influences employee performance through work discipline in air transportation research and transportation development agencies.